The periodontal treatment and the prevention of cardiovascular diseases: integrative literature review (Research, Society and Development, 2023)
Periodontal diseases (PDs) are among the most prevalent inflammatory diseases and have the etiology in microbial infections. Studies reveal the possibility of association between local inflammations and other organs of the body, favoring the spread of oral pathogens. The aim of this study was to conduct an integrative review in order to discuss the relevance of periodontal treatment as an ally in the prevention of cardiovascular diseases (CVDs) and as auxiliary treatment of these diseases. For this, the data were collected using the descriptors in English and Portuguese: ("cardiovascular disease and periodontal disease"; "cardiovascular disease and periodontal disease and inflammation"; cardiovascular disease and periodontal disease and prevention") with clipping between the years 2017-2022. After established inclusion criteria (human studies, regardless of gender, clinical studies, observational, meta-analyses, systematic reviews, publications in portuguese, english and spanish) and exclusion (articles with other approaches on PDs and CVDs different from aspects of the prevention of PDs), the articles were selected for analysis. The results revealed 52 articles that, after excluding the studies: presented theme leak, did not answer the research question or were duplicated, resulting in a total of 26 articles. The present study pointed out that most studies point to an association between apical periodontitis and cardiovascular disease, highlighting the need to approach the subject in the professional training of dentists and the importance of clinical research that corroborates existing studies, favoring greater elucidation of the theme and greater development in management of clinical cases.